Pressure ulcers in surgery patients: incidence and associated factors - Scarlatti, Kelly Cristina; Michel, Jeanne Liliane Marlene; Gamba, Mônica Antar; Gutiérrez, Maria Gaby Rivero de (Revista da Escola de Enfermagem da USP, 2011)
Pressure ulcers are an important perioperatory care quality indicator This is a longitudinal case series study, performed with the following objectives: to estimate the incidence of pressure ulcers in patients submitted to medium and large surgeries; rate them according to the stage and location; verify the association with the variables: gender, age, body mass index (BMI), co-morbidities, surgical position, duration of surgery, anesthesia type and use of positioning devices, with presence or absence of pressure ulcers. Data collection took place in 2007 in São Paulo, with 199 patients, 20.6% of which presented pressure ulcers, and most (98.6%) in stages I and II, and the main location was the trunk (35.1%). The variables: position, surgery time, general anesthesia, and device use had a statistically significant association. In conclusion, there is a high incidence of pressure ulcers among surgical patients, requiring actions aimed at reducing this type of injury.